A Natural Semantic Language Approach to Dawan Verb ‘To Take’ - Maria Gaudensiana Sona; I Wayan Budiarta (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2018)
This research investigates the study of Natural Semantic Metalanguage (NSM) to the verb mait 'to take' of Dawan - East Nusa Tenggara Province, Indonesia. Typically the study describes the semantic structure and the semantic role of the argument of the mait. I made use of Goddard’s theory of NSM (Goddard, 1997) in dealing with the verb analysis. Data were obtained from 5 Dawan native informants. Results of data analysis show that the verb of Dawan has a significant meaning in line with the concept of semantic of the verb mait